Penanaman Nilai Karakter Melalui Metode Bernyanyi di RA Muslimat Tanwirut Thullab - Vitaria Agustina; Siti Nur Aini (Alzam: Journal of Islamic Early Childhood Education, 2021)
This study aims to determine the inculcation of character values ​​through the singing method in RA Muslimat Tanwirut Thullab Plumpang Tuban. This type of research is qualitative research. The research data were collected using observation, interviews, and documentation. The results are singing method is carried out in four steps, including determining the song according to the theme, using a familiar song tone, introducing the song, singing together. One of the supporting factors of the implementation of the singing method on the character of the students of RA Muslimat Tanwirut Thullab Plumpang Tuban, one of which is that singing is an activity that is very liked by students, while the inhibiting factor of the implementation of the singing method on student character is singing which makes students disorderly. and not well conditioned.